Natural Antimicrobials Promote the Anti-Oxidative Inhibition of COX-2 Mediated Inflammatory Response in Primary Oral Cells Infected with Staphylococcus aureus, Streptococcus pyogenes and Enterococcus faecalis - Eugenia Butucel; Igori Balta; Iulia Adelina Bundurus; Cosmin Alin Popescu; Tiberiu Iancu; Adelina Venig; Ioan Pet; Ducu Stef; David McCleery; Lavinia Stef; Nicolae Corcionivoschi (MDPI AG, 2023)
Staphylococcus aureus, Streptococcus pyogenes and Enterococcus faecalis can colonize the tooth root canals, adhere to dentin walls, and frequently cause periodontitis in dogs. Bacterial periodontal diseases are common in domesticated pets, causing severe oral cavity inflammation and a strong immune response. This study investigates the antioxidant effect of a natural antimicrobial mixture (Auraguard-Ag) on the ability of S. aureus, S. pyogenes and E. faecalis to infect primary canine oral epithelial cells as well as its impact on their virulence factors. Our data show that a concentration of 0.25% Ag is sufficient to inhibit the growth of all three pathogens, whereas a concentration of 0.5% will become bactericidal. The sub-inhibitory concentration of 0.125% Ag reveals that the antimicrobial mixture can significantly reduce biofilm formation and exopolysaccharide production. The impact on these virulence factors was further translated into a significantly reduced ability to infect primary canine oral epithelial cells and restore epithelial tight junctions, with no impact on the epithelial cell viability. The post-infection inflammatory cytokines (IL-1β and IL-8) and the COX-2 mediator were also reduced both in mRNA and protein expression levels. The oxidative burst, detected upon infection, was also decreased in the presence of Ag, as our results show a significant decrease in H2O2 released by the infected cells. We show that inhibition of either NADPH or ERK activity will result in a downregulation of COX-2 expression and lower levels of H2O2 in infected cells. Conclusively, our study shows that natural antimicrobials reduce pro-inflammatory events, post infection, through an antioxidative mechanism that involves the downregulation of the COX-2 mediator via the inactivation of ERK in the absence of H2O2. As a result, they significantly reduce the risk of secondary bacterial infections and host oxidative stress caused by Staphylococcus aureus, Streptococcus pyogenes and Enterococcus faecalis accumulation in biofilms in an in vitro canine oral infection model.